KOMPARASI PENINGKATAN INKLUSI KEUANGAN DAN INDIKATOR PEMBANGUNAN DI INDONESIA - Akyuwen, Roberto; Mangowal, Caroline (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2018)
The level of financial inclusion depicts public participation or access of financial products and services provided by financial institutions in a country. Such access is viewed essential, because it illustrates the opportunity of a more prosperous life for the society. The results of a survey conducted by the Financial Services Authority of Indonesia shows that financial inclusion in Indonesia has increased in considerably rapid pace in the last few years. However, is the improvement of conditions for financial inclusion in line with the improvements to the indicators of development in Indonesia? The study was intended to answer this question. Analysis tools used are descriptive statistics by making use of secondary data available on the Financial Services Authority and the Central Bureau of Statistics. Based on the results of the analysis it can be concluded that improvements to financial inclusion apparently has not been able to contribute positively towards the many indicators of development of Indonesia. Various improvements are necessary in order for increased financial inclusion to be transmitted effectively to the improvement of welfare of the population of Indonesia.Â Keywords: access, financial inclusion, indicators of development.